Evaluation of the nutritional properties and the antioxidant activity of rice bean (Vigna umbellata) seeds collected in Sơn La province - Luyen, Le Hong; Linh, Nguyen Trang; Thanh, Nguyen Chi; Anh, Le Thi Van (Vietnam Journal of Biotechnology, 2024)
Vigna umbellata is an underutilized species in Vietnam, and more information about its nutritional values needs to be provided. This study investigated the nutritional composition and antioxidant activity of the seeds of 10 rice bean varieties collected from different districts of Son La province. Moisture content, ash and nutritional composition, including total protein, lipid, and carbohydrate were estimated. The 2,2-Diphenyl-1-picrylhydrazyl (DPPH) scavenging assay, total phenolic content (TPC), and total flavonoid content (TFC) were carried out to assess the antioxidant activity. The results showed as follows: moisture content ranged from 0.44% to 1.23%, total ash values were obtained in the range between 38.46 and 45.72 mg/g DW, total protein content spread from 106.65 to 156.77 mg/g; total lipid varied from 7.37 to 11.90 mg/g, and total carbohydrate dominated the nutritional profile with 786.10 to 834.73 mg/g. Remarkably, there were significant differences (p < 0.05 using ANOVA) among the rice bean species from various districts of Son La province regarding moisture and protein content. Still, similar values were observed for other parameters (p > 0.05). The IC50 of the DPPH assay ranged from 259.06 µg/mL to 479.99 µg/mL, while the TPC varied from 2.85 to 4.98 mg GAE/g, and TFC values were in the range between 6.46 and 13.73 mg QE/g DW. Both TPC and TFC were significantly negatively correlated to antioxidant activity. This study is the first report on the nutritional compositions and antioxidant activity in the seeds of 10 rice bean varieties collected in Son La province. The findings in this study contribute to valorizing the V. umbellata species, which might be a promising plant as a low-priced staple food for ethnic people in mountainous regions.